A Review on Health Benefits of Cuminum Cyminum (Cumin) (International Journal of Innovative Research in Engineering & Management, 2023)
Spices are the elements that give food its  taste. Food's fragrance, texture, and color are its main  purposes. They also serve as a preservative, as well as  providing nutritional and physiological advantages. Cumin  (Cuminum cyminum) is a blooming plant in the Apiaceae  family that is locally known as "zeera." Many eastern  cuisines call for it as a condiment and seasoning. Cumin is  well-known for its anti-oxidant properties. Seed spices  affect a number of biological systems, such as the digestive,  circulatory, reproductive, or neurological systems, causing  a range of metabolic but also physiologic consequences.  Antioxidants, antidiabetic, anticancer, antimicrobial  activity, hypolipidemic influence, insecticidal, beneficial in  heavy menstrual bleeding, aiding digestion, high blood  pressure, instrumentation of enzymes involved, immune  function, reduction of inflammatory process, molecular  mechanism, modulations of immune systems, The  purpose of this research is to have a thorough analysis on  the present trends in research here on health advantages of  four common seed seasonings: cumin, coriander, but also  fennel.
Keywords: Antioxidants; Cuminum Cyminum; Cumin; Essential Oils; Spices